Security dialogue
Security Dialogue aims to combine cutting-edge advances in theory with new empirical findings across a range of fields relevant to the study of security. Security Dialogue provides an outlet for new approaches and methodologies from disciplines such as gender studies, political sociology, political economy, political theory, international relations, religious studies, visual arts, anthropology, psychoanalysis and political philosophy.